Novel Graphene Oxide/Zinc Phthalocyanine Composites Bearing 3-Chloro-4-Fluorophenoxy: Potential Usage for Sono/Photochemical Applications - Guensel, Armagan; Mutlu, Nazire; Yasa Atmaca, Goeknur; Guensel, Hilal; Bilgicli, Ahmet T.; Erdogmus, Ali; Niluefer Yarasir, M. (WILEY-V C H VERLAG GMBH, 2023)
The aim of this paper is to explore the therapeutic contribution of graphene oxide (GO) to new sono/photosensitizers through sono/photochemical studies for the first time. For this purpose, new zinc (II) phthalocyanine bearing 3-chloro-4-fluorophenoxy 2 was synthesized and then its GO-based composites were prepared by non-covalently coating ZnPc 2 on the graphene oxide surface. The photoactivity of these materials was compared and discussed in terms of their potential ability to be used in photosensitizer in photodynamic therapy (PDT) and sono-photodynamic therapy (SPDT). In these application areas, GO can serve as photosensitizer carrier, while ZnPc 2 can be acting as PDT/SPDT agent. Therefore, phthalocyanine composites containing different percentages of graphene oxide by weight (wt.% GO) were prepared. SEM (scanning electron microscopy) results supported the interaction between GO and ZnPc 2. In the sono-photochemical study, both ZnPc 2 and its composites gave very higher phi(Delta) values than the photochemical study. The sono-photochemical phi(Delta) values were found to be 0.928 for 0 wt.% GO, 0.869 for 0.25 wt.% GO, 0.891 for 0.50 wt.% GO, 0.868 for 1 wt.% GO, 0.908 for 3 wt.% GO, 0.845 for 5 wt.% GO and 0.851 for 10 wt.% GO, respectively. According to obtained results, these materials could be promise as good photosensitizers for both the photochemical study and the sono-photochemical study due to their very high singlet oxygen generation.
Keywords: Graphene Oxide; Photosensitizer; Phthalocyanine; Sono; Photodynamic Therapy; Synthesis; DELIVERY; CANCER; FUNCTIONALIZATION; SUBSTITUENTS; HYBRID; Chemistry